Formulation, Development and Evaluation of Praziquantel Loaded Nanosponges (PZQ-Nsgs) by Using Factorial Design - Reddy, Raju Balaji; Nakra, Dr. Vinod; Singh Saluja, Dr. Manmeet (Journal of Biomedical and Pharmaceutical Research, 2023)
Introduction: Praziquantel is used to treat diseases caused by infection with numerous types of internal/gastrointestinal and external parasites. Aim: The aim of this study was to design, formulate and evaluation of Praziquantel loaded nanosponges (PZQ-NSGs) by using factorial design. Methodology: The Determination of Calibration curve by UV visible spectrophotometer and Analytical method validation by UV visible spectrophotometer. The Analytical Techniques Used to Detect Drug-Excipient Compatibility of drug.Results and Discussion: The developed nanosponge drug delivery system were subjected to stability testing at higher temperature and humidity condition i.e. at 40⁰C ± 2⁰C and RH 75% ± 5 % after 6 months as per ICH guidelines. Solid state characterization of freeze dried PZQ-NSGs have been done with FTIR, PXRD, particle size analysis. From above characterization it was observed that, the sample was remained stable at 40⁰C ± 2⁰C and RH 75% ± 5 % even after 6 months.Conclusion: Formulated nanosponges formulation was found to be stable at accelerated stability conditions as per ICH guidelines up to 6 months. Nanosized distribution, amorphous nature, better encapsulation and inclusion complexation with EC were found to be the major drivers for significant improvement in solubility, nanosized particles, dissolution efficiency and stability.